Analysis of Biennial Peak Discharges in the Lower Kening River Using the Nakayasu Method - Novita Putri, Ayuning Tyas; Mushthofa; Yulia Indriani (Rekayasa Sipil, 2024)
Flooding is a persistent and challenging issue in many regions, requiring precise methods for estimating peak flood discharge to improve flood management strategies. Accurate discharge estimates are essential for designing effective flood control infrastructure and implementing mitigation measures. This study uses the Nakayasu Synthetic Unit Hydrograph (SUH) method to estimate peak flood discharge for a 2-year return period in the Kening River Flow Area, Parengan sub-district, Tuban district, and East Java Province. This research used various methods for rainfall analysis, including the Gumbel, Pearson III, and log-normal distributions. In contrast, rainfall intensity calculations were carried out using the Mononobe and ABM methods. The research highlights the effectiveness of these methods in predicting rainfall intensity and peak discharge, providing valuable insights for flood management practices. The results show that the Nakayasu SUH method predicts a peak discharge of 206.62 m³/second. By improving the accuracy of flood discharge predictions, this study supports better planning and design of flood control structures, which is crucial for managing flood risks and enhancing infrastructure resilience in flood-prone areas. These findings are expected to improve flood management practices and infrastructure planning.